From Literary Chronicle to Advertisement: a literacy practice (Research, Society and Development, 2020)
This study presents a proposal for literacy practice, having as its starting point the literary chronicle “The strange procedure by Dona Dolores”, written by Luis Fernando Verissimo (1995), in which the central character makes advertisements for products used in her family routine. Students are required to create a product for the prevention of Covid-19 contamination and elaborate an advertisement for this product approaching the pandemic context and using digital tools. This study has as main objective to propose a literacy practice with the production of audiovisual materials through an advertisement for the community, by making them aware of the care and prevention items regarding the world pandemic, in a humorous way. To achieve this objective, the  theoretical support is based on the studies by Rojo (2009, 2013), Cosson (2014, 2017), Brazil (2018), among other scholars. As a methodological basis, it relies on qualitative research, with articulated actions for high school students, focusing on exploratory aspects of research. Considering this literacy practice, a didactic suggestion for the pandemic moment is displayed, reconciling the multi-obstacles to the social and cultural context experienced by the population. In this way, the lesson planning presented in this article can be adapted to different realities, even when the school situation returns to the classroom environment in its entirety.